Prostate Cancer Genetics: Variation by Race, Ethnicity, and Geography - Rebbeck, Timothy R. (Seminars in radiation oncology, 2017)
Prostate cancer rates vary substantially by race, ethnicity, and geography. These disparities can be explained by variation in access to screening and treatment, variation in exposure to prostate cancer risk factors, and variation in the underlying biology of prostate carcinogenesis (including genomic propensity of some groups to develop biologically aggressive disease). It is clear that access to screening and access to treatment are critical influencing factors of prostate cancer rates; yet, even among geographically diverse populations with similar access to care (eg, low- and medium-income countries), African descent men have higher prostate cancer rates and poorer prognosis. To date, the proportion of prostate cancer that can be explained by environmental exposures is small, and the effect of these factors across different racial, ethnic, or geographical populations is poorly understood. In contrast, prostate cancer has one of the highest heritabilities of all major cancers. Numerous genetic susceptibility markers have been identified from family-based studies, candidate gene association studies, and genome-wide association studies. Some prostate cancer loci, including the risk loci found at chromosome 8q24, have consistent effects in all groups studied to date. However, replication of many susceptibility loci across race, ethnicity, and geography remains limited, and additional studies in certain populations (particularly in men of African descent) are needed to better understand the underlying genetic basis of prostate cancer.